Fundamentals of antennas : concepts and applications - Christodoulou, Christos G., 1955- (SPIE tutorial texts ;, 2001)
This tutorial explains antenna design and application for various systems, including communications, remote sensing, radar, and biomedicine. It describes basic wire and array antennas in detail and introduces other types such as reflectors, lenses, horns, Yagi, microstrip, and frequency-independent antennas. Integration issues and technical challenges are discussed. Aimed at students, engineers, researchers, and technical professionals.